Synthesis process of aluminum hypophosphite synergistic system flame-retardant polyamide
By mechanically polishing and modifying aluminum hypophosphate, and combining coupling agent and triphenyl phosphate, the problem of large amount of inorganic flame retardant added to polyamide materials is solved, and the effect of improving the flame retardant and environmentally friendly properties of polyamide composite materials is achieved.
Patent Information
- Application Number
- CN202411555961.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, after the inorganic flame retardant is added to the polyamide material, there is a problem of large amount of addition and poor compatibility with the material, which affects the mechanical properties of the polyamide composite material.
The surface modification of aluminum hypophosphate was performed by mechanical grinding method, combining aluminate coupling agent and rare earth aluminate coupling agent to form a mesh crosslinked macromolecular structure, and triphenyl phosphate was used as a synergistic agent to improve the compatibility of aluminum hypophosphate in PA6 composite materials.
The initial decomposition temperature and thermal degradation rate of the flame retardant material are reduced, the residual carbon amount and flame retardant performance of the polyamide composite material are improved, and the environmental protection performance of the material is enhanced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyamide materials, and in particular to a synthesis process and a preparation method of an aluminum hypophosphite synergistic system flame-retardant polyamide. Background Art
[0002] PA6 material has the advantages of good mechanical properties, electrical properties, heat resistance and light weight. It can replace metal materials in some application fields and is mainly used in building materials equipment, packaging materials, automotive electrical appliances, medical equipment and household appliances. As the earliest product produced in engineering plastics, PA6 is also the product with the largest demand and output among polyamide finished products. It is estimated that the demand for PA6 in my country will increase at an average annual rate of 9% in the past decade, and the domestic demand for polyamide 6 will reach 900,000 tons by 2024.
[0003] The limiting oxygen index (LOI) of PA6 during combustion is only 21%, and a large number of melt droplets are generated during the combustion process, which poses a great safety hazard in its application and seriously threatens the safety of people's lives and property. With the advancement of science and technology, the development of industry and the increasingly stringent fire safety standards, the performance requirements for PA6 are also getting higher and higher. Therefore, the flame retardant modification of PA6 materials is of great significance and is an important synthetic process direction in the industrial application of PA6.
[0004] Based on this, the patent technical document with Chinese publication number CN108587148A discloses a glass fiber reinforced PA6 flame retardant material, which uses aluminum hydroxide (ATH), magnesium hydroxide (MH), aluminum diethylphosphinate (ADP) as flame retardants, and KH-550 as a coupling agent to prepare glass fiber reinforced flame retardant polyamide 6 (PA6). The results show that when the glass fiber addition amount is 50 parts, the coupling agent dosage is 1.5%, and the total amount of flame retardant is 72 parts and remains unchanged, MH and ATH are compounded as flame retardants. When m (MH): m (ATH) = 3:1, the tensile strength is 100.97 MPa, the flexural strength is 156.27 MPa, the oxygen index can reach 31.8%, and the vertical burning test result is UL94 V-2, with ATH and ADP compounded as flame retardant, when m (ATH): m (ADP) = 5:1, under the optimal process conditions, at 800 ° C, the residual carbon rate can reach 45.93% and 43.51% respectively; an obvious carbon layer appears during combustion. This dense protective layer effectively blocks the heat source from the PA6 matrix, thereby protecting the matrix from further combustion and improving the flame retardant properties of PA6.
[0005] However, the flame retardant technical solution disclosed above still has technical problems such as large addition amount and poor compatibility with materials. Specifically, although inorganic flame retardants have the advantages of low smoke, low toxicity, low corrosiveness, good thermal stability, and environmental friendliness; however, such additives generally have technical problems such as large addition amount and poor compatibility with materials; thus, after being added to polyamide materials, the mechanical properties of polyamide materials will be significantly reduced. More specifically, at present, aluminum hydroxide (ATH) is widely used as a flame retardant improvement additive for materials due to its advantages of high stability, non-toxicity, tastelessness, low price and easy availability; such flame retardants mainly absorb heat during the decomposition of compounds, and use the generated water vapor to dilute the oxygen concentration around the combustion area. At the same time, the residues generated by them may prevent the transfer of heat and oxygen. However, traditional ATH must have the disadvantages of large particle size, low decomposition temperature, and poor flame retardant efficiency. If it is directly added to the flame retardant probability scheme of polyamide, it will inevitably affect the mechanical properties of the polyamide composite material system. Summary of the invention
[0006] Based on this, it is necessary to provide a synthesis process for flame-retardant polyamide with an aluminum hypophosphite synergistic system to address the technical problems of large addition amount and poor compatibility with materials of inorganic flame retardants in the prior art.
[0007] A synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide, comprising the following steps: S1: Preparing the pretreatment materials according to the preset ratio: aluminum hypophosphite, aluminate coupling agent, rare earth aluminate coupling agent and triphenyl phosphate; S2: using a mechanical grinding method to perform surface modification on the pre-prepared pre-treatment material to obtain modified aluminum hypophosphite; S3: preparing extrusion materials according to preset ratios: modified aluminum hypophosphite, PA6 pellets, epoxy silicone resin and toluene; S4: drying the modified aluminum hypophosphite and PA6 pellets in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the materials; S5: placing epoxy silicone resin in toluene, stirring thoroughly to make the epoxy resin completely dissolved in toluene; S6: The dried modified aluminum hypophosphite and PA6 pellets are placed in a high-speed mixer and mixed for 30 minutes, and then the epoxy silicone resin dissolved in toluene is placed in the high-speed mixer, and the mixing and stirring is continued for 5 minutes; S7: placing the mixed materials in a twin-screw extruder for extrusion and granulation; S8: placing the prepared pellets in a vacuum drying oven and drying them at 80° C. for 8 hours to obtain a flame-retardant polyamide composite material with an aluminum hypophosphite synergistic system.
[0008] Specifically, in the aforementioned step S2, the surface of the pre-prepared pre-treatment material is modified by mechanical grinding to obtain the modified aluminum hypophosphite in the following process steps: S21: drying the aluminum hypophosphite in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the material; S22: putting aluminum hypophosphite and rare earth aluminate coupling agent in a preset ratio into a planetary ball mill equipped with grinding balls with preset weights, and setting the parameters of the ball milling to: intermittent unidirectional operation for 60 minutes, stop for 5 minutes, and repeat this operation for 5 times; S23: continuing to add a preset ratio of aluminate coupling agent into the planetary ball mill, the parameters of the ball mill are set to: intermittent bidirectional operation for 30 minutes, stop for 10 minutes, and repeat this operation for 3 times; S24: Take out the modified aluminum hypophosphite from the planetary ball mill for later use.
[0009] Specifically, in step S22, the weight of the grinding balls is set to: the weight of the grinding balls ≥ (the weight of the aluminum hypophosphite + the weight of the rare earth aluminate coupling agent) * 3.
[0010] Specifically, the preset ratio of the pre-treatment material is: 46-50 parts of aluminum hypophosphite, 0.5-4 parts of aluminate coupling agent, 1-2 parts of rare earth aluminate coupling agent and 0.4-0.5 parts of triphenyl phosphate, calculated by weight.
[0011] Specifically, the preset ratio of the pre-treatment material is: 49 parts of aluminum hypophosphite, 1 part of aluminate coupling agent, 1 part of rare earth aluminate coupling agent and 0.5 part of triphenyl phosphate, calculated by weight.
[0012] Specifically, 46 parts of aluminum hypophosphite, 4 parts of aluminate coupling agent, 1.9 parts of rare earth aluminate coupling agent and 0.4 parts of triphenyl phosphate.
[0013] Specifically, the preset ratio of the extrusion material is: 17-21 parts of modified aluminum hypophosphite, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 3-6 parts of toluene, calculated by weight.
[0014] Specifically, the preset ratio of the extrusion material is: 17 parts of modified aluminum hypophosphite, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 3 parts of toluene, calculated by weight.
[0015] Specifically, the preset ratio of the extrusion material is: 18 parts, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 6 parts of toluene, calculated by mass.
[0016] Specifically, the preset ratio of the extrusion material is: 17 parts, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 3 parts of toluene, calculated by mass.
[0017] In summary, the synthesis process of the aluminum hypophosphite synergistic system flame-retardant polyamide of the present invention first modifies the surface of the aluminum hypophosphite material by mechanical grinding; at the same time, respectively coordinates an aluminate coupling agent and a rare earth aluminate coupling agent to react to generate a network cross-linked macromolecular structure, and uses a small molecule substance triphenyl phosphate as a synergist to improve the compatibility of aluminum hypophosphite in the PA6 composite material system; then, the modified aluminum hypophosphite prepared in the above steps is used as a flame retardant, and epoxy silicone resin is dissolved in toluene as a synergistic component to reduce the initial decomposition temperature and thermal degradation rate of the polyamide composite flame retardant material, thereby increasing the residual carbon content of the polyamide composite material. More specifically, in the aluminum hypophosphite flame retardant synergistic system disclosed in the present invention, the addition of modified aluminum hypophosphite can reduce the initial decomposition temperature and thermal degradation rate of the flame retardant material and increase the residual carbon content of the material. The addition of epoxy resin can reduce the SPR and TSP of the flame retardant system and improve the environmental performance of the material; at the same time, it makes the surface of the carbon layer of the polyamide composite material dense and continuous after combustion, with extremely small holes, and the carbon content in the residue increases, which promotes the carbonization performance of the polyamide composite material. That is, this flame retardant system can make the surface of the carbon layer of the polyamide composite material dense and continuous after combustion, with a network cross-linked structure, and the phosphorus content of the system is increased, which improves the flame retardant performance of the material without adding a large amount of flame retardant ingredients. Therefore, the synthesis process of the aluminum hypophosphite synergistic system flame retardant polyamide of the present invention solves the technical problems of large addition amount and poor compatibility with materials of inorganic flame retardants in the prior art. DETAILED DESCRIPTION
[0018] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation mode of the present invention is described in detail below in conjunction with embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0019] Specifically, the synthesis process of the aluminum hypophosphite synergistic system flame retardant polyamide of the present invention comprises the following steps: S1: Preparing the pretreatment materials according to the preset ratio: aluminum hypophosphite, aluminate coupling agent, rare earth aluminate coupling agent and triphenyl phosphate; S2: using a mechanical grinding method to perform surface modification on the pre-prepared pre-treatment material to obtain modified aluminum hypophosphite; S3: preparing extrusion materials according to preset ratios: modified aluminum hypophosphite, PA6 pellets, epoxy silicone resin and toluene; S4: drying the modified aluminum hypophosphite and PA6 pellets in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the materials; S5: placing epoxy silicone resin in toluene, stirring thoroughly to make the epoxy resin completely dissolved in toluene; S6: The dried modified aluminum hypophosphite and PA6 pellets are placed in a high-speed mixer and mixed for 30 minutes, and then the epoxy silicone resin dissolved in toluene is placed in the high-speed mixer, and the mixing and stirring is continued for 5 minutes; S7: placing the mixed materials in a twin-screw extruder for extrusion and granulation; S8: The prepared pellets are placed in a vacuum drying oven and dried at 80° C. for 8 hours to obtain a flame-retardant polyamide composite material with an aluminum hypophosphite synergistic system.
[0020] Specifically, phosphorus-based flame retardants, as the core additive of halogen-free flame retardants, are considered to be a promising method due to their high flame retardant efficiency. Phosphorus-based flame retardants are divided into organic phosphorus-based and inorganic flame retardants. Compared with organic phosphorus-based flame retardants, inorganic phosphorus-based flame retardants have the advantages of good thermal stability, low cost and environmental friendliness, and are more popular. Aluminum hypophosphite, as a typical inorganic phosphorus-based flame retardant, has the characteristics of environmental friendliness and high efficiency, but aluminum hypophosphite has poor water resistance and strong hygroscopicity, which is not conducive to storage, transportation and use.
[0021] At present, the commonly used modification methods of aluminum hypophosphite include microencapsulation method, compound synergy, ultrafine method, surface modification, etc. However, the microencapsulation method, compound synergy, ultrafine method and other methods have certain limitations in improving water resistance; therefore, choosing surface modification to improve the water resistance of aluminum hypophosphite is a more feasible technical means; especially using coupling agent method to modify the surface hydrophobicity of aluminum hypophosphite. Furthermore, although silane coupling agent can improve the compatibility of aluminum hypophosphite with epoxy resin; however, the flammability of silane coupling agent is not conducive to the flame retardant effect of aluminum hypophosphite. Therefore, coupling agents with flame retardant synergy function such as aluminate coupling agent and rare earth aluminate coupling agent are selected to modify aluminum hypophosphite, which can improve its compatibility and flame retardant effect; previously, mechanical force surface composite method can also be used to improve the efficiency of coupling agent surface modification.
[0022] Specifically, mechanical grinding is a good method for surface modification, which is a method for converting external force, that is, mechanical force, into chemical energy. Mechanical force surface composite method is a good method for green chemistry, which provides a method to effectively reduce or even completely avoid the use of solvents. This method has the advantages of saving time in synthesis, being environmentally friendly and more economical, high yield, and easy recycling; therefore, this technical means has good practicality and sustainability.
[0023] More specifically, in the aforementioned step S2, the surface modification treatment of the pre-prepared pre-treatment material is performed by mechanical grinding to obtain the modified aluminum hypophosphite, and the specific process includes the following steps: S21: drying the aluminum hypophosphite in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the material; S22: putting aluminum hypophosphite and rare earth aluminate coupling agent in a preset ratio into a planetary ball mill equipped with grinding balls with preset weights, and setting the parameters of the ball milling to: intermittent unidirectional operation for 60 minutes, stop for 5 minutes, and repeat this operation for 5 times; S23: continuing to add a preset ratio of aluminate coupling agent into the planetary ball mill, the parameters of the ball mill are set to: intermittent bidirectional operation for 30 minutes, stop for 10 minutes, and repeat this operation for 3 times; S24: Take out the modified aluminum hypophosphite from the planetary ball mill for later use.
[0024] Specifically, in the aforementioned step S22, the weight of the grinding ball is set as follows: the weight of the grinding ball ≥ (the weight of aluminum hypophosphite + the weight of the rare earth aluminate coupling agent) * 3; for example, the weight of the aluminum hypophosphite input is 50g, and the weight of the rare earth aluminate coupling agent is 0.5g; then the weight of the grinding ball should be at least 151.5g.
[0025] Specifically, coupling agents are widely used in surface modification of flame retardants mainly because there are two types of groups in the chemical structure of coupling agents. One is the inorganic-philic group, and the other is the organic-philic group. This is very promising for the combination between inorganic phosphorus flame retardants and organic resins. During the use of coupling agents, the inorganic-philic end can be combined with the inorganic phosphorus flame retardant, and the organic-philic end can be combined with the organic polymer. With the help of this effect with the coupling agent, a good interface bonding can be achieved between the inorganic flame retardant and the organic polymer with greatly different surface properties, so as to improve the interface performance between the matrix resin and the inorganic flame retardant.
[0026] Thus, the synthesis process of the aluminum hypophosphite synergistic system flame-retardant polyamide of the present invention proposes a technical means for surface modification of aluminum hypophosphite using an aluminate coupling agent and a rare earth aluminate coupling agent, wherein the aluminate coupling agent, as an important surfactant, has high surface reactivity and is environmentally friendly. Its structural formula is: (RO)xAl(OCR')m·Dn, and there are two different functional groups in the aluminate coupling agent -(RO)x represents a hydrophilic group, -(OCR)m represents a hydrophobic group, and Dn represents a coordination group. The hydrophilic group can react chemically with the polar group on the surface of the inorganic flame retardant to reduce the surface energy of the aluminum hypophosphite. The prepared superhydrophobic material has good environmental stability. Furthermore, the rare earth aluminate coupling agent, as a surfactant, can improve the interface properties of the organic resin and the inorganic flame retardant, so as to play a synergistic modification effect in the surface modification process of the aluminum hypophosphite.
[0027] Furthermore, although aluminum hypophosphite has the advantages of high phosphorus content, good thermal stability, and low price and availability, when the amount of flame retardant added is small, the flame retardant PA6 material will show a "pole climbing phenomenon" during combustion, and the compatibility of aluminum hypophosphite with PA6 material is poor. In order to overcome the shortcomings of aluminum hypophosphite and improve the performance of flame retardant materials, when surface modification of aluminum hypophosphite is performed, a small molecule substance triphenyl phosphate is added as a synergist. The triphenyl phosphate will be evenly mixed with aluminum hypophosphite during the ball milling process, so that the modified aluminum hypophosphite can be migrated to the surface of the PA6 composite material during extrusion, thereby improving the compatibility of the modified aluminum hypophosphite with the PA6 material, so as to achieve the purpose of improving the flame retardant properties of the PA6 material.
[0028] Specifically, for the aforementioned step S1, the specific proportions of the four pre-treatment materials are as follows, calculated by weight: Pre-treatment material example 1: 50 parts of aluminum hypophosphite, 0.5 parts of aluminate coupling agent, 1 part of rare earth aluminate coupling agent and 0.5 parts of triphenyl phosphate.
[0029] Pre-treatment material example 2: 49 parts of aluminum hypophosphite, 1 part of aluminate coupling agent, 1 part of rare earth aluminate coupling agent and 0.5 part of triphenyl phosphate.
[0030] Pre-treatment material example 3: 48 parts of aluminum hypophosphite, 2 parts of aluminate coupling agent, 2 parts of rare earth aluminate coupling agent and 0.5 parts of triphenyl phosphate.
[0031] Pre-treatment material example 4: 46 parts of aluminum hypophosphite, 4 parts of aluminate coupling agent, 1.9 parts of rare earth aluminate coupling agent and 0.4 parts of triphenyl phosphate.
[0032] The experimental methods for the hydrophobicity and water resistance of modified aluminum hypophosphite are as follows: Hydrophobicity test: The water contact angle of the flame retardant is characterized by using a JY-82 static water contact angle meter. Hydrophobicity test of flame retardant polyamide composites: First, 100 grams of aluminum hypophosphite and modified aluminum hypophosphite are placed in the mold of a tablet press, and then pressed into sheets under a certain pressure using a tablet press. Second, the static water contact angle of the sample is tested using a JY-82 water contact angle tester.
[0033] Water resistance test: Water resistance test of modified aluminum hypophosphite: add 0.5g of aluminum hypophosphite and modified hypophosphorous acid into a sample bottle with 35ml of deionized water, observe and record the phenomenon. The observation period is 180 days.
[0034] Using the aforementioned hydrophobicity test method, it can be seen that the water contact angle of aluminum hypophosphite is only 9.78°, indicating that aluminum hypophosphite has good hydrophilicity. The water contact angles of the modified aluminum hypophosphite prepared by pre-treatment material examples 1-4 have changed greatly, and are all greater than 90°. Specifically: The water contact angle of the pre-treated material Example 1 is: 118.55°; The water contact angle of the pre-treated material Example 2 is: 98.46°; The water contact angle of the pre-treated material Example 3 is: 125.62°; The water contact angle of the pre-treated material in Example 4 is 106.88°.
[0035] It can be seen that the modification process has caused a qualitative change in the surface properties of aluminum hypophosphite, a complete transformation from hydrophilicity to hydrophobicity.
[0036] It can be known from the aforementioned water resistance test method that when aluminum hypophosphite is just added to the water medium, it is clearly seen that the aluminum hypophosphite is evenly dispersed in the water and presents a milky white color, indicating that aluminum hypophosphite has a strong hydrophilicity in water. After standing for 1 hour, part of the aluminum hypophosphite is dissolved in water. After 8 hours, only a small amount of undissolved aluminum hypophosphite at the bottom of the aluminum hypophosphite in the water, and the rest of the aluminum hypophosphite is completely dissolved in water. Compared with standing for 8 hours, the aluminum hypophosphite after standing for 180 days did not show any change. This phenomenon can further prove that aluminum hypophosphite has poor water resistance and is not conducive to long-term storage. It combines with water in the surrounding environment during transportation and use, reducing the effectiveness of aluminum hypophosphite. In contrast, the pre-treatment material Example 1 has poor dispersibility. Part of the modified aluminum hypophosphite of Example 1 directly settles to the bottom of the sample bottle, while part of the modified aluminum hypophosphite floats on the water. After standing for one hour, it can be seen that aluminum hypophosphite and modified aluminum hypophosphite have different degrees of sedimentation, but it is obvious that the sedimentation rate of modified aluminum hypophosphite is faster than that of aluminum hypophosphite, and most of the modified aluminum hypophosphite is precipitated at the bottom of the sample bottle. After 180 days of immersion, it was found that a large part of the modified aluminum hypophosphite was still floating in the water as flocs, while the aluminum hypophosphite was completely dissolved; this experimental result also shows that modified aluminum hypophosphite has good water resistance.
[0037] Furthermore, in the aforementioned step S3, the ratio of different extrusion materials is as follows, in parts by mass: Comparative Example: PA6, 120 parts.
[0038] Example 11: 17 parts of modified aluminum hypophosphite prepared from the pre-treated material Example 1, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 3 parts of toluene; Example 12: 21 parts of modified aluminum hypophosphite prepared from the pre-treated material Example 1, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 6 parts of toluene; Example 13: 18 parts of modified aluminum hypophosphite prepared from the pre-treated material Example 1, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 6 parts of toluene.
[0039] Further, each of the embodiments 11-13 can be evaluated by evaluating its LOI index and vertical burning test (UL-94). The specific experimental results are shown in Table 1 below: Table 1: Flame retardant properties of PA6 composite materials with modified aluminum hypophosphite synergistic system
[0040] It can be seen from the flame retardant test results in Table 1 above that in different embodiment ratios, the synthesis process of the aluminum hypophosphite synergistic system flame retardant polyamide of the present invention can obtain a polyamide composite material with excellent flame retardant properties.
[0041] In summary, the synthesis process of the aluminum hypophosphite synergistic system flame-retardant polyamide of the present invention first modifies the surface of the aluminum hypophosphite material by mechanical grinding; at the same time, respectively coordinates an aluminate coupling agent and a rare earth aluminate coupling agent to react to generate a network cross-linked macromolecular structure, and uses a small molecule substance triphenyl phosphate as a synergist to improve the compatibility of aluminum hypophosphite in the PA6 composite material system; then, the modified aluminum hypophosphite prepared in the above steps is used as a flame retardant, and epoxy silicone resin is dissolved in toluene as a synergistic component to reduce the initial decomposition temperature and thermal degradation rate of the polyamide composite flame retardant material, thereby increasing the residual carbon content of the polyamide composite material. More specifically, in the aluminum hypophosphite flame retardant synergistic system disclosed in the present invention, the addition of modified aluminum hypophosphite can reduce the initial decomposition temperature and thermal degradation rate of the flame retardant material and increase the residual carbon content of the material. The addition of epoxy resin can reduce the SPR and TSP of the flame retardant system and improve the environmental performance of the material; at the same time, it makes the surface of the carbon layer of the polyamide composite material dense and continuous after combustion, with extremely small holes, and the carbon content in the residue increases, which promotes the carbonization performance of the polyamide composite material. That is, this flame retardant system can make the surface of the carbon layer of the polyamide composite material dense and continuous after combustion, with a network cross-linked structure, and the phosphorus content of the system is increased, which improves the flame retardant performance of the material without adding a large amount of flame retardant ingredients. Therefore, the synthesis process of the aluminum hypophosphite synergistic system flame retardant polyamide of the present invention solves the technical problems of large addition amount and poor compatibility with materials of inorganic flame retardants in the prior art.
[0042] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0043] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide, characterized in that: It includes the following steps: S1: Preparing the pretreatment materials according to the preset ratio: aluminum hypophosphite, aluminate coupling agent, rare earth aluminate coupling agent and triphenyl phosphate; S2: using a mechanical grinding method to perform surface modification on the pre-prepared pre-treatment material to obtain modified aluminum hypophosphite; S3: preparing extrusion materials according to preset ratios: modified aluminum hypophosphite, PA6 pellets, epoxy silicone resin and toluene; S4: placing the modified aluminum hypophosphite and PA6 pellets in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the materials; S5: placing epoxy silicone resin in toluene, stirring thoroughly to make the epoxy resin completely dissolved in toluene; S6: The dried modified aluminum hypophosphite and PA6 pellets are placed in a high-speed mixer and mixed for 30 minutes, and then the epoxy silicone resin dissolved in toluene is placed in the high-speed mixer, and the mixing and stirring is continued for 5 minutes; S7: placing the mixed materials in a twin-screw extruder for extrusion and granulation; S8: placing the prepared pellets in a vacuum drying oven and drying them at 80° C. for 8 hours to obtain a flame-retardant polyamide composite material with an aluminum hypophosphite synergistic system.
2. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 1, characterized in that: In the aforementioned step S2, the surface of the pre-prepared pre-treatment material is modified by mechanical grinding to obtain the modified aluminum hypophosphite in the following process steps: S21: drying the aluminum hypophosphite in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the material; S22: putting aluminum hypophosphite and rare earth aluminate coupling agent in a preset ratio into a planetary ball mill equipped with grinding balls with preset weights, and setting the parameters of the ball milling to: intermittent unidirectional operation for 60 minutes, stop for 5 minutes, and repeat this operation for 5 times; S23: continuing to add a preset ratio of aluminate coupling agent into the planetary ball mill, the parameters of the ball mill are set to: intermittent bidirectional operation for 30 minutes, stop for 10 minutes, and repeat this operation for 3 times; S24: Take out the modified aluminum hypophosphite from the planetary ball mill for later use.
3. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 2, characterized in that: In step S22, the weight of the grinding balls is set to: the weight of the grinding balls ≥ (the weight of the aluminum hypophosphite + the weight of the rare earth aluminate coupling agent) * 3.
4. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 3, characterized in that: The preset ratio of the pre-treatment materials is: 46-50 parts of aluminum hypophosphite, 0.5-4 parts of aluminate coupling agent, 1-2 parts of rare earth aluminate coupling agent and 0.4-0.5 parts of triphenyl phosphate, calculated by weight.
5. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 4, characterized in that: The preset ratio of the pre-treatment material is: 49 parts of aluminum hypophosphite, 1 part of aluminate coupling agent, 1 part of rare earth aluminate coupling agent and 0.5 parts of triphenyl phosphate, calculated by weight.
6. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 4, characterized in that: 46 parts of aluminum hypophosphite, 4 parts of aluminate coupling agent, 1.9 parts of rare earth aluminate coupling agent and 0.4 parts of triphenyl phosphate.
7. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 1, characterized in that: The preset ratio of the extrusion material is: 17-21 parts of modified aluminum hypophosphite, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 3-6 parts of toluene, calculated by mass.
8. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 1, characterized in that: The preset ratio of the extrusion material is: 17 parts of modified aluminum hypophosphite, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 3 parts of toluene by mass.
9. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 1, characterized in that: The preset ratio of the extrusion material is: 18 parts, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 6 parts of toluene by mass.
10. The synthesis process of aluminum hypophosphite synergistic system flame retardant polyamide according to claim 1, characterized in that: The preset ratio of the extrusion material is: 17 parts, 100 parts of PA6 pellets, 3 parts of epoxy silicone resin and 3 parts of toluene by mass.
Citation Information
Patent Citations
Method for preparing glass fiber-enhanced PA6 flame-retardant material
CN108587148A
High-melt-index long-glass-fiber-reinforced PA6 (polyamide 6) plastic and preparation method thereof
CN106883602A